Achieving equity in UHC interventions: who is left behind by neglected tropical disease programmes in Cameroon? - Makia Christine Masong; Kim Ozano; Marlene Siping Tagne; Marlene Ntchinda Tchoffo; Sharon Ngang; Rachael Thomson; Sally Theobald; Louis-Albert Tchuem Tchuenté; Estelle Kouokam (Taylor & Francis Group, 2021)
Background: The UN's Sustainable Development Goals (SDGs) which pledge to leave no one behind for Universal health coverage (UHC) raise the importance of ensuring equitable health outcomes and healthcare delivery. As Neglected Tropical Diseases (NTDs) affect the most disadvantaged and hard to reach populations, they are considered a litmus test for Universal health coverage. Objective: Here, we assess the challenges of implementing Mass Drug Administrations (MDAs) for schistosomiasis prevention and control, in a context of expanded treatment where both community and school-based distribution were carried out, assessing which groups are missed and developing strategies to enhance equity. Methods: This is a qualitative study applying ethnographic observations, in-depth interviews (109) and focus group discussions (6) with key informants and other community members. Participants included community drug distributors, teachers, health workers, and implementing partners across four schistosomiasis endemic regions in Cameroon. Data collected were analysed thematically. Results: Programme implementation gaps have created circumstances where indigenous farmers (originally from the region) and migrating farmers (not originally from the region known as 'strangers' and 'farm hands'), women of reproductive age and school-aged children are continuously missed in MDA efforts in Cameroon. Key implementation challenges that limit access to MDA within this context include inadequate sensitization campaigns that don't sufficiently build trust with different groups; limits in CDD training around pregnancy and reproductive health; lack of alignment between distribution and community availability and the exclusion of existing formal and informal governance structures that have established trusting community relationships. Conclusion: Through identifying key populations missed in MDAs within specific contexts, we highlight how social inclusion and equity could be increased within the Cameroonian context. A main recommendation is to strengthen trust at the community level and work with established partnerships and local governance structures that can support sustainable solutions for more equitable MDA campaigns.